A conceptual Kano and Quality Function Deployment (QFD) framework for healthcare service - Norshahrizan, Nordin; Razli, Che Razak (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.